Deaths Attributed to Respiratory Syncytial Virus in Young Children in High–Mortality Rate Settings: Report from Child Health and Mortality Prevention Surveillance (CHAMPS). (2nd September 2021) - Blau, Dianna M; Baillie, Vicky L; Els, Toyah; Mahtab, Sana; Mutevedzi, Portia; Keita, Adama Mamby; Kotloff, Karen L; Mehta, Ashka; Sow, Samba O; Tapia, Milagritos D; Tippett Barr, Beth A; Oluoch, Benard O; et al.
Abstract: Background: Lower respiratory tract infections are a leading cause of death in young children, but few studies have collected the specimens needed to define the role of specific causes. The Child Health and Mortality Prevention Surveillance (CHAMPS) platform aims to investigate causes of death in children aged <5 years in high–mortality rate settings, using postmortem minimally invasive tissue sampling and other advanced diagnostic techniques. We examined findings for deaths identified in CHAMPS sites in 7 countries in sub-Saharan Africa and south Asia to evaluate the role of respiratory syncytial virus (RSV). Methods: We included deaths that occurred between December 2016 and December 2019. Panels determined causes of deaths by reviewing all available data including pathological results from minimally invasive tissue sampling, polymerase chain reaction screening for multiple infectious pathogens in lung tissue, nasopharyngeal swab, blood, and cerebrospinal fluid samples, clinical information from medical records, and verbal autopsies. Results: We evaluated 1213 deaths, including 695 in neonates (aged <28 days), 283 in infants (28 days to <12 months), and 235 in children (12–59 months). RSV was detected in postmortem specimens in 67 of 1213 deaths (5.5%); in 24 deaths (2.0% of total), RSV was determined to be a cause of death, and it contributed to 5 other deaths. Younger infants (28 days to <6 months of age) accounted for half of all deaths attributed to RSV; 6.5% of all deaths in younger infants were attributed to RSV. RSV was the underlying and only cause in 4 deaths; the remainder (n = 20) had a median of 2 (range, 1–5) other conditions in the causal chain. Birth defects (n = 8) and infections with other pathogens (n = 17) were common comorbid conditions. Conclusions: RSV is an important cause of child deaths, particularly in young infants. These findings add to the substantial body of literature calling for better treatment and prevention options for RSV in high–mortality rate settings.